Metal and nonmetal cascade catalyst with Fe-B double sites as well as preparation method and application of metal and nonmetal cascade catalyst
By synthesizing metal and non-metallic cascade catalysts with Fe-B double-sites on graphene oxide support, the low site density and catalyst deactivation problems of Fe-N-C catalysts in practical applications are solved, and efficient quaternary electron oxygen reduction reaction and excellent stability are achieved.
Patent Information
- Application Number
- CN202411738525.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-29
AI Technical Summary
In practical applications, existing Fe-N-C catalysts have problems such as low site density, low desorption efficiency of oxygen intermediates and serious catalyst deactivation, making it difficult to achieve excellent activity and stability.
Metal and non-metallic cascade catalysts with Fe-B double-sites were synthesized by hydrothermal synthesis and chemical vapor deposition technology. Fe-O-B structure was formed on graphene oxide support through ferric nitrate and boric acid as iron and boron sources, and Fe utilization and site density were improved.
The catalyst exhibits excellent tetraelectron oxygen reduction electrocatalytic performance in alkaline environments, has high half-wave potential and kinetic current density, and the current density decreases by only 5% in long-term stability tests, proving its excellent stability and application prospects.
Smart Images

Figure HDA0005162067170000011 
Figure HDA0005162067170000012 
Figure HDA0005162067170000013
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemical catalysis, and particularly relates to a metal and non-metal cascade catalyst with Fe-B dual sites, and a preparation method and application thereof. Background Art
[0002] The cathodic oxygen reduction reaction (ORR) is an important half-reaction that determines the performance and efficiency of various electrochemical energy devices, such as hydrogen fuel cells and rechargeable metal-air batteries. However, achieving efficient and fast ORR kinetics remains a major challenge due to the complexity of the multi-electron transfer process. To date, platinum group metal (PGM) materials have been used as benchmark electrocatalysts for catalyzing ORR, but their high cost and natural scarcity have seriously hindered their large-scale application. Therefore, people have been working hard to explore cheap, efficient and durable alternatives to PGM materials. Currently, atomically dispersed metal-nitrogen-carbon (MNC, M=Fe, Co, Ni, etc.) materials with minimal economic cost and variable coordination structure have attracted great interest. In particular, Fe-NC catalysts with FeN4 structure are considered to be the most promising alternatives to PGM materials due to their good ORR performance. However, in practical applications, the performance of Fe-NC still needs to be further optimized, and the challenges it faces include low site density, low desorption efficiency of oxygen intermediates from Fe centers, and severe catalyst deactivation. Therefore, it is urgent to develop efficient ORR electrocatalysts with dense active sites to regulate the adsorption behavior of intermediates, thereby achieving excellent activity and stability. Summary of the invention
[0003] The purpose of the present invention is to provide a metal and non-metal cascade catalyst with a Fe-B dual site and a preparation method and application thereof, so as to solve the technical problem that the Fe-B dual site coordination structure is difficult to control;
[0004] In order to achieve the above object, the technical solution adopted by the present invention is:
[0005] A metal and non-metal cascade catalyst with Fe-B dual sites and a preparation method and application thereof, comprising the following steps:
[0006] S1. Adding boric acid to the graphene oxide solution, and then adding ferric nitrate, and ultrasonicating to obtain a homogeneous precursor solution, and subjecting the precursor solution to a hydrothermal reaction to obtain a black columnar reaction product;
[0007] S2. The reaction product is freeze-dried and then subjected to high-temperature nitridation by chemical vapor deposition to obtain a metal and non-metal cascade catalyst having a Fe-B dual site.
[0008] Preferably, the percentage of iron in the ferric nitrate to the mass of graphene oxide in the graphene oxide solution is 1-10%; the percentage of boron in the boric acid to the mass of graphene oxide in the graphene oxide solution is 1-7%, wherein deionized water is used to dissolve the ferric nitrate nonahydrate and the boric acid.
[0009] Preferably, the preparation method of the graphene oxide solution is: dissolving graphene oxide solid in deionized water, ultrasonicating for 4-6 hours to obtain a uniformly dispersed graphene oxide solution; the concentration of the graphene oxide solution is 1-3 mg mL -1 .
[0010] Preferably, in step S1, the ultrasonic time is 10 min.
[0011] Preferably, in step S1, the temperature of the hydrothermal reaction is 170-190° C., and the time of the hydrothermal reaction is 8-14 h.
[0012] Preferably, in step S2, the freeze-drying treatment time is 5-10 hours.
[0013] Preferably, in step S2, the high-temperature nitridation using chemical vapor deposition method includes the following steps: nitridation is carried out in a mixed atmosphere of argon and ammonia, the reaction temperature is 700-900°C, the reaction time is 1-3h, the argon flow rate is 100±10sccm, and the ammonia flow rate is 50±10sccm.
[0014] Another aspect of the present invention provides a metal and non-metal cascade catalyst having a Fe-B dual site, which is prepared by the above-mentioned preparation method.
[0015] In another aspect, the present invention provides the use of the above-mentioned metal and non-metal cascade catalyst with Fe-B dual sites as a catalyst for four-electron oxygen reduction reaction.
[0016] Another aspect of the present invention provides the use of the above-mentioned metal and non-metal cascade catalyst with Fe-B dual sites as a cathode catalyst for a zinc-air battery.
[0017] The present invention uses ferric nitrate (Fe(NO3)3) as an iron source, boric acid (H3BO3) as a boron source, and ammonia (NH3) as a nitrogen source, and adopts hydrothermal synthesis and chemical vapor deposition technology (CVD) to synthesize a metal and non-metal cascade catalyst with Fe-B dual sites. The catalyst exhibits excellent four-electron oxygen reduction electrocatalytic performance in an alkaline environment.
[0018] The present invention uses graphene as a carrier and boric acid as a modifier of the carbon substrate in a hydrothermal reaction, which not only provides a large number of anchoring sites for Fe atoms, but also facilitates the formation of a Fe-OB structure. In the hydrothermal reaction, high temperature effectively catalyzes the dehydration condensation reaction between the hydroxyl functional groups in graphene oxide and H3BO3, so that the B atoms are uniformly combined into the graphite structure in the form of BO3 oxygen anions. Afterwards, these oxygen anions are gradually converted into boron carbide (BC 3-x O x ,x=0-2), destroying sp 2 The electrical neutrality of carbon creates additional anchoring sites for the iron ions. The Fe-OB bridge bond was obtained through the hydrothermal self-assembly process, which significantly improved the utilization rate and site density of Fe. During the CVD process, ammonia easily decomposes to produce N radicals with lone pairs of electrons, which easily coordinate with Fe ions. Ultimately, the Fe cation coordinates with two BC2O groups and two N radicals; these same groups are located in the para position, destroying the D 4h symmetry, thus forming a Fe-B double-site structure.
[0019] The synthesis method of the present invention is simple, the preparation cycle is short, the precursor is cheap and the reserves are abundant, and it has good application prospects. The metal and non-metal cascade catalyst with Fe-B dual sites can be obtained by simple hydrothermal and chemical vapor deposition. When the catalyst is used as a cathode catalyst for anion exchange membrane fuel cells and zinc-air batteries, it exhibits excellent power density and stability, and has very broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The XRD pattern of the metal and non-metal cascade catalyst with Fe-B dual sites prepared in Example 1;
[0021] Figure 2 This is a Raman spectrum of the metal and non-metal cascade catalyst with Fe-B dual sites prepared in Example 1;
[0022] Figure 3 This is an infrared spectrum of the metal and non-metal cascade catalyst with Fe-B dual sites prepared in Example 1;
[0023] Figure 4 TEM image of the metal and non-metal cascade catalyst with Fe-B dual sites prepared in Example 1, where: a-500nm, b-200nm;
[0024] Figure 5 Schematic diagram of element contents of the metal and non-metal cascade catalyst with Fe-B dual sites prepared in Example 1;
[0025] Figure 6 This is the XPS graph of the metal and non-metal cascade catalyst with Fe-B dual sites prepared in Example 1, where: a-Fe 2p, bB 1s, cN 1s, dO 1s;
[0026] Figure 7 The basic 4e of the metal and non-metal cascade catalyst with Fe-B dual sites prepared in Example 1 - ORR performance, where: a-polarization curve, b-corresponding Koutecky-Levich (KL) plot;
[0027] Figure 8 The basic 4e of the metal and non-metal cascade catalyst with Fe-B dual sites prepared in Example 1 - ORR performance, where: a-Tafel slope plot, b-stability curve;
[0028] Fig. 9 The discharge polarization curve and power density diagram of the metal and non-metal cascade catalyst with Fe-B dual sites prepared in Example 1 in a zinc-air battery device;
[0029] Fig.10 Polarization curve and power density curve of the metal and non-metal cascade catalyst with Fe-B dual sites prepared in Example 1 under 1.0 bar back pressure in H2-O2 AEMFCs;
[0030] Fig.11 The metal and non-metal cascade catalyst with Fe-B dual sites prepared in Example 1 was tested for a long term in AEMFCs at 0.6 V under H2-air conditions. DETAILED DESCRIPTION
[0031] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments.
[0032] The graphene oxide in the following examples is prepared by a modified Hummers method, and the specific process is as follows: 3 g of graphite powder and a mixed solution of concentrated H2SO4 and H3PO4 (volume ratio 9:1) are added to a three-necked flask, and 18 g of KMnO4 solid is slowly added at a rotation speed of 200-350 rpm.
[0033] The water bath temperature was set at 50°C, the stirring speed was set at 200-350 rpm, and the stirring time was set at 12 h. After the reaction, the solution temperature dropped to room temperature, and then poured into 400 mL of pre-frozen deionized water and stirred evenly. H2O2 was slowly added to the solution in small amounts several times until the solution changed from purple to bright yellow. The solution was repeatedly washed with 30% by mass HCl solution, deionized water, anhydrous ethanol and ether in turn. A light yellow graphene oxide solid was obtained after vacuum drying at room temperature for 24 h.
[0034] Example 1
[0035] A method for preparing a metal and non-metal cascade catalyst having a Fe-B dual site, the steps are as follows:
[0036] 0.16 g of graphene oxide solid was added to 80 ml of deionized water. After ultrasonic treatment for 6 hours, 3 mL of boric acid solution and 6 mL of ferric nitrate nonahydrate solution were successively added to the graphene oxide solution, wherein the mass of iron and boron elements accounted for 6% and 3% of the mass of graphene oxide, respectively. After ultrasonic treatment for 10 minutes, a uniformly dispersed precursor solution was obtained.
[0037] The precursor solution was transferred to the inner lining of the reactor, and the hydrothermal temperature was set to 180°C; the hydrothermal time was set to 12 h.
[0038] After the hydrothermal product was freeze-dried for 10 hours, the obtained product was placed in a CVD furnace and subjected to high-temperature nitridation reaction in a mixed atmosphere of Ar and NH3 using chemical vapor deposition technology. The reaction parameters were set as follows: temperature: 800°C, gas flow rate: NH3: 50sccm, Ar: 100sccm, and nitridation time of 2h. A metal and non-metal cascade catalyst (Fe-BNC-3) with a Fe-B dual site was obtained.
[0039] Example 2
[0040] A method for preparing a metal and non-metal cascade catalyst having a Fe-B dual site, the steps are as follows:
[0041] 0.16 g of graphene oxide solid was added to 80 ml of deionized water. After ultrasonic treatment for 6 hours, 7 mL of boric acid solution and 6 mL of ferric nitrate nonahydrate solution were successively added to the graphene oxide solution, wherein the mass of iron and boron elements accounted for 6% and 7% of the mass of graphene oxide, respectively. After ultrasonic treatment for 10 minutes, a uniformly dispersed precursor solution was obtained.
[0042] The precursor solution was transferred to the inner lining of the reactor, and the hydrothermal temperature was set to 180°C; the hydrothermal time was set to 12 h.
[0043] After the hydrothermal product was freeze-dried for 10 hours, the obtained product was placed in a CVD furnace and subjected to high-temperature nitridation reaction in a mixed atmosphere of Ar and NH3 using chemical vapor deposition technology. The reaction parameters were set as follows: temperature: 800°C, gas flow rate: NH3: 50sccm, Ar: 100sccm, and nitridation time of 2h. A metal and non-metal cascade catalyst (Fe-BNC-7) with a Fe-B dual site was obtained.
[0044] Example 3
[0045] A method for preparing a metal and non-metal cascade catalyst having a Fe-B dual site, the steps are as follows:
[0046] 0.16 g of graphene oxide solid was added to 80 ml of deionized water. After ultrasonic treatment for 6 hours, 3 mL of boric acid solution and 6 mL of ferric nitrate nonahydrate solution were successively added to the graphene oxide solution, wherein the mass of iron and boron elements accounted for 6% and 3% of the mass of graphene oxide, respectively. After ultrasonic treatment for 10 minutes, a uniformly dispersed precursor solution was obtained.
[0047] The precursor solution was transferred to the inner lining of the reactor, and the hydrothermal temperature was set to 180°C; the hydrothermal time was set to 12 h.
[0048] After the hydrothermal product was freeze-dried for 10 hours, the obtained product was placed in a CVD furnace and subjected to high-temperature nitridation reaction in a mixed atmosphere of Ar and NH3 using chemical vapor deposition technology. The reaction parameters were set as follows: temperature: 800°C, gas flow rate: NH3: 50sccm, Ar: 100sccm, and nitridation time: 1h. A metal and non-metal cascade catalyst (Fe-BNC@1) with a dual Fe-B site was obtained.
[0049] Example 4
[0050] A method for preparing a metal and non-metal cascade catalyst having a Fe-B dual site, the steps are as follows:
[0051] 0.16 g of graphene oxide solid was added to 80 ml of deionized water. After ultrasonic treatment for 6 hours, 3 mL of boric acid solution and 6 mL of ferric nitrate nonahydrate solution were successively added to the graphene oxide solution, wherein the mass of iron and boron elements accounted for 6% and 3% of the mass of graphene oxide, respectively. After ultrasonic treatment for 10 minutes, a uniformly dispersed precursor solution was obtained.
[0052] The precursor solution was transferred to the inner lining of the reactor, and the hydrothermal temperature was set to 180°C; the hydrothermal time was set to 12 h.
[0053] After the hydrothermal product was freeze-dried for 10 hours, the obtained product was placed in a CVD furnace and subjected to high-temperature nitridation reaction in a mixed atmosphere of Ar and NH3 using chemical vapor deposition technology. The reaction parameters were set as follows: temperature: 800°C, gas flow rate: NH3: 50sccm, Ar: 100sccm, and nitridation time: 3h. A metal and non-metal cascade catalyst (Fe-BNC@3) with a dual Fe-B site was obtained.
[0054] Example 5
[0055] A method for preparing a metal and non-metal cascade catalyst having a Fe-B dual site, the steps are as follows:
[0056] 0.16 g of graphene oxide solid was added to 80 ml of deionized water. After ultrasonic treatment for 6 hours, 3 mL of boric acid solution and 6 mL of ferric nitrate nonahydrate solution were successively added to the graphene oxide solution, wherein the mass of iron and boron elements accounted for 6% and 3% of the mass of graphene oxide, respectively. After ultrasonic treatment for 10 minutes, a uniformly dispersed precursor solution was obtained.
[0057] The precursor solution was transferred to the inner lining of the reactor, and the hydrothermal temperature was set to 180°C; the hydrothermal time was set to 12 h.
[0058] After the hydrothermal product was freeze-dried for 10 hours, the obtained product was placed in a CVD furnace and subjected to high-temperature nitridation reaction in a mixed atmosphere of Ar and NH3 using chemical vapor deposition technology. The reaction parameters were set as follows: temperature: 850°C, gas flow rate: NH3: 50sccm, Ar: 100sccm, and nitridation time of 2h. A metal and non-metal cascade catalyst with Fe-B dual sites (Fe-BNC / 850) was obtained.
[0059] Example 6
[0060] A method for preparing a metal and non-metal cascade catalyst having a Fe-B dual site, the steps are as follows:
[0061] 0.16 g of graphene oxide solid was added to 80 ml of deionized water. After ultrasonic treatment for 6 hours, 3 mL of boric acid solution and 6 mL of ferric nitrate nonahydrate solution were successively added to the graphene oxide solution, wherein the mass of iron and boron elements accounted for 6% and 3% of the mass of graphene oxide, respectively. After ultrasonic treatment for 10 minutes, a uniformly dispersed precursor solution was obtained.
[0062] The precursor solution was transferred to the inner lining of the reactor, and the hydrothermal temperature was set to 180°C; the hydrothermal time was set to 12 h.
[0063] After the hydrothermal product was freeze-dried for 10 hours, the obtained product was placed in a CVD furnace and subjected to high-temperature nitridation reaction in a mixed atmosphere of Ar and NH3 using chemical vapor deposition technology. The reaction parameters were set as follows: temperature: 950°C, gas flow rate: NH3: 50sccm, Ar: 100sccm, and nitridation time of 2h. A metal and non-metal cascade catalyst with Fe-B dual sites (Fe-BNC / 950) was obtained.
[0064] Example 7
[0065] A method for preparing a metal and non-metal cascade catalyst having a Fe-B dual site, the steps are as follows:
[0066] 0.16 g of graphene oxide solid was added to 80 ml of deionized water. After ultrasonic treatment for 6 hours, 3 mL of boric acid solution and 10 mL of ferric nitrate nonahydrate solution were successively added to the graphene oxide solution, wherein the mass of iron and boron elements accounted for 10% and 3% of the mass of graphene oxide, respectively. After ultrasonic treatment for 10 minutes, a uniformly dispersed precursor solution was obtained.
[0067] The precursor solution was transferred to the inner lining of the reactor, and the hydrothermal temperature was set to 180°C; the hydrothermal time was set to 12 h.
[0068] After the hydrothermal product was freeze-dried for 10 hours, the obtained product was placed in a CVD furnace and subjected to high-temperature nitridation reaction in a mixed atmosphere of Ar and NH3 using chemical vapor deposition technology. The reaction parameters were set as follows: temperature: 800°C, gas flow rate: NH3: 50sccm, Ar: 100sccm, and nitridation time of 2h. A metal and non-metal cascade catalyst (Fe-BNC-3) with a Fe-B dual site was obtained.
[0069] Example 8
[0070] A method for preparing a metal and non-metal cascade catalyst having a Fe-B dual site, the steps are as follows:
[0071] 0.16 g of graphene oxide solid was added to 80 ml of deionized water. After ultrasonic treatment for 6 hours, 1 mL of boric acid solution and 6 mL of ferric nitrate nonahydrate solution were successively added to the graphene oxide solution, wherein the mass of iron and boron elements accounted for 6% and 1% of the mass of graphene oxide, respectively. After ultrasonic treatment for 10 minutes, a uniformly dispersed precursor solution was obtained.
[0072] The precursor solution was transferred to the inner lining of the reactor, and the hydrothermal temperature was set to 180°C; the hydrothermal time was set to 12 h.
[0073] After the hydrothermal product was freeze-dried for 10 hours, the obtained product was placed in a CVD furnace and subjected to high-temperature nitridation reaction in a mixed atmosphere of Ar and NH3 using chemical vapor deposition technology. The reaction parameters were set as follows: temperature: 800°C, gas flow rate: NH3: 50sccm, Ar: 100sccm, and nitridation time of 2h. A metal and non-metal cascade catalyst (Fe-BNC-1) with a Fe-B dual site was obtained.
[0074] Example 9
[0075] A method for preparing a metal and non-metal cascade catalyst having a Fe-B dual site, the steps are as follows:
[0076] 0.16 g of graphene oxide solid was added to 80 ml of deionized water. After ultrasonic treatment for 6 hours, 3 mL of boric acid solution and 1 mL of ferric nitrate nonahydrate solution were added to the graphene oxide solution in sequence, wherein the mass of iron and boron elements accounted for 1% and 3% of the mass of graphene oxide, respectively. After ultrasonic treatment for 10 minutes, a uniformly dispersed precursor solution was obtained.
[0077] The precursor solution was transferred to the inner lining of the reactor, and the hydrothermal temperature was set to 180°C; the hydrothermal time was set to 12 h.
[0078] After the hydrothermal product was freeze-dried for 10 hours, the obtained product was placed in a CVD furnace and subjected to high-temperature nitridation reaction in a mixed atmosphere of Ar and NH3 using chemical vapor deposition technology. The reaction parameters were set as follows: temperature: 800°C, gas flow rate: NH3: 50sccm, Ar: 100sccm, and nitridation time of 2h. A metal and non-metal cascade catalyst (Fe-BNC-3) with a Fe-B dual site was obtained.
[0079] The catalyst performance of Example 1 was evaluated and characterized as follows:
[0080] Metallic and nonmetallic cascade catalysts with Fe-B dual sites were used as 4e - ORR catalyst materials: The test instrument uses pine rotating disk electrode equipment (Rotating disk electrode, RDE and Rotating ring-diskelectrode, RRDE; electrode model: AFE6R2) to carry out relevant electrochemical tests. The dispersion liquid is formulated as follows: 10 mg of catalyst is added to 1 mL of deionized water, 1 mL of anhydrous ethanol and 200 μL of Nafion solution and then ultrasonicated for 1 hour. Take 2.5 μL of the dispersion droplet and apply it on the disk electrode (disk area of RDE: 0.196 cm 2 Or the disk area of RRDE: 0.2376 cm 2 The area of the platinum ring is 0.2356 cm 2), and then 2.5 μL of the dispersion was applied after the first dispersion dried (the area mass loading of the electrocatalyst was 0.12 mg cm -2 (RDE) or 0.10 mg cm -2 (RRDE)), and after natural drying for 6-10 hours, relevant experimental tests can be carried out. Three-electrode system: platinum wire electrode as counter electrode, Ag / AgCl (3M KCl solution as salt bridge) as reference electrode, disk electrode or ring disk electrode coated with metal and non-metal cascade catalyst with Fe-B dual site as working electrode. Before the experiment, nitrogen or oxygen was introduced into 0.1M KOH electrolyte until saturated, and the reaction temperature was 100mV s -1 The cyclic voltammetry (CV) test was used to activate the catalyst for 30-60 min until there was no air on the catalyst surface. In an oxygen-saturated electrolyte, different speeds (225-2025 rpm) were set and the voltage range was 0.1-1.1 V at 5 mV s -1 Linear voltammetry (LSV) was performed at a scan rate of 1.
[0081] Membrane electrode assembly (MEA) and anion exchange membrane fuel cell test: First, 10 mg of electrocatalyst, 2000 μL of isopropanol, 200 μL of ultrapure water and 200 μL of PiperION-B5-HCO3 solution (5 wt%) were mixed by ultrasound for 2 hours to prepare catalyst ink. Then, the catalyst ink was sprayed on one side of polytetrafluoroethylene treated carbon paper (Sigracet, 29BC) with a microporous layer (MPL), keeping the electrode area 2*2 cm 2 Fe-BNC or commercial Pt / C was used as the cathode catalyst, and the final catalyst loading was 2.0 mg cm -2 and 0.4 mg cm -2 Pt / C (60%, Johnson Matthey) was used as the anode catalyst with a loading of 0.4 mg cm -2 . The prepared carbon paper containing anode and cathode catalysts was placed on both sides of the anion exchange membrane (Versogen, PiperION-A-20HCO3) to prepare MEA. Polarization curve and stability tests were performed under H2-O2 or H2-Air conditions using an NBT-FEM-100W fuel cell test system equipped with a back pressure module. During the test, the anode and cathode humidity was adjusted to 100%, and the H2 and O2 or air flow was maintained at 0.6L min -1 The stability of the H2-Air fuel cell was evaluated at a constant cell voltage of 0.6V.
[0082] Zinc-air battery assembly and testing: Cathode electrode: Take 5 mg of homemade catalyst and 5 mg of carbon black powder, add 50 μL of isopropanol, 25 μL of polytetrafluoroethylene solution (PTFE) and 0.95 mL of deionized water, and ultrasonicate for 3 to 5 hours to disperse evenly. The obtained dispersion is drop-coated on the surface of 2.5*2.5 cm hydrophilic carbon paper, with a drop-coating area of 1*1 cm and a loading of 1.0 mg cm -2 ; Anode electrode: Use anhydrous ethanol and acetone to ultrasonically clean the polished zinc plate for 30 minutes. Battery electrolyte: A mixed solution of 6M KOH and 0.2M ZnCl2.
[0083] After testing, the half-wave potential can reach 0.91V, and the kinetic current density at 0.85V is 16.98mA cm -2 , with good stability and extremely low H2O2 selectivity, proving that the catalyst has good 4e - ORR performance.
[0084] Figure 1 Shown is the XRD pattern of the metal and non-metal cascade catalyst with Fe-B dual sites prepared in Example 1. The two broad diffraction peaks near 25° and 44° are assigned to graphitized carbon, and no peaks of iron-related substances are detected, indicating that the iron element exists in the lattice of graphitic carbon in the form of isolated atoms or clusters.
[0085] Figure 2 The Raman spectrum of the metal and non-metal cascade catalyst with Fe-B dual sites prepared in Example 1 is shown. In the Raman spectrum, the intensity ratio of the D band to the G band of Fe-BNC (I D / I G ) is 1.17. This is because boron atoms are generally in the form of BC 3-x O x Compared with N element, B atom will cause larger lattice distortion and form defect-rich material.
[0086] Figure 3 The infrared spectrum of the metal and non-metal cascade catalyst with Fe-B dual sites prepared in Example 1 is shown. Fe-BNC has abundant functional groups, such as CN and CO groups, which effectively alleviate the inherent inertness of the graphene basal surface.
[0087] Figure 4 a and 4b are the low-magnification and high-magnification TEM images of the metal and non-metal cascade catalyst with Fe-B dual sites prepared in Example 1, respectively. The morphology of Fe-BNC presents an ultrathin nanosheet structure with abundant wrinkles and ripples, which is beneficial to the adsorption and activation of oxygen in the ORR process.
[0088] Figure 5Shown is a schematic diagram of the element content of the metal and non-metal cascade catalyst with Fe-B dual sites prepared in Example 1, wherein Fe: 0.73, B: 0.98, C: 87.32, N: 5.81, O: 5.15, indicating that iron, boron and nitrogen elements are successfully doped into graphene.
[0089] Figure 6 The XPS graph of the metal and non-metal cascade catalyst with Fe-B dual sites prepared in Example 1 is shown. In the Fe 2p spectrum, the Fe 2p at 710.6 eV and 714.7 eV 3 / 2 The XPS peaks are assigned to Fe 2+ and Fe 3+ state, and Fe 2+ The peak intensity of Fe 3+ The strong peaks confirmed that the Fe atoms mainly existed in the form of divalent cations. The B 1s spectrum was deconvoluted into three peaks, belonging to the structures of BC3 (189.4 eV), BC2O (190.6 eV) and BCO2 (192.0 eV), respectively. The samples all had a large amount of BC2O structure and no Fe-B signal. In addition, the N 1s spectrum showed that the main nitrogen species were pyridinic-N and Fe-N, which constituted the key active sites for ORR. The O 1s spectrum showed that there were various oxygen functional groups in the sample, such as Fe-O (530.3 eV), C=O (531.6 eV), OB (532.8 eV) and CO (533.5 eV).
[0090] Figure 7 The metal and nonmetal cascade catalyst with Fe-B dual sites prepared in Example 1 is shown in alkaline 4e - ORR performance, polarization curves and corresponding Koutecky-Levich (KL) plots in 0.1 M KOH electrolyte, where the catalyst has a high half-wave potential (E 1 / 2 , 0.91 V) and kinetic current density (J K At 0.85 V, 16.98 mA cm -2 ). Furthermore, the electron transfer number (n) was calculated from the KL plot, and the n value of the catalyst was 4.00, indicating an ideal 4-electron transfer pathway.
[0091] Figure 8 The metal and nonmetal cascade catalyst with Fe-B dual sites prepared in Example 1 is shown in alkaline 4e - ORR performance, where Figure 8 a and Figure 8 b are the Tafel slope graph and stability curve in 0.1 M KOH electrolyte, respectively. The Tafel slope of the catalyst is 74 mV dec-1 , demonstrating the fast kinetics. After 110 h of long-term stability testing, the current density of Fe-BNC only decreased by 5%, highlighting the superior electrocatalytic stability of Fe-BNC.
[0092] Fig. 9 The figure shows the discharge polarization curve and power density diagram of the metal and non-metal cascade catalyst with Fe-B dual sites prepared in Example 1 in a zinc-air battery device. The above catalyst is used as the cathode catalyst of the zinc-air battery, which can provide 195 mW cm -2 The peak power density of 2.13 W / m2 / cm2 proves that the catalyst has both excellent catalytic activity and stable performance and also has prospects for practical application.
[0093] Fig.10 The figure shows the metal and non-metal cascade catalyst with Fe-B dual sites prepared in Example 1. The polarization curve and power density curve of H2-O2 AEMFCs under 1.0 bar back pressure. The peak power density of AEMFCs with Fe-BNC as cathode is 690 mW cm -2 .
[0094] Fig.11 The metal and non-metal cascade catalyst with Fe-B dual sites prepared in Example 1 is shown in the long-term test of AEMFCs at 0.6V under H2-air conditions. Specifically, the Fe-BNC-based AEMFCs show excellent durability, with only a 12% loss in current density after 350 hours. The above results show that Fe-BNC has excellent ORR activity and excellent stability under actual AEMFCs operating conditions, highlighting the broad potential of Fe-BNC in energy device applications.
Claims
1. A method for preparing a metal and non-metal cascade catalyst having a Fe-B dual site, characterized in that: The following steps are involved: S1. Adding a boron source to a graphene oxide solution, and then adding an iron source, performing ultrasound to obtain a precursor solution, and subjecting the precursor solution to a hydrothermal reaction to obtain a reaction product; S2. The reaction product is freeze-dried and then subjected to high-temperature nitridation by chemical vapor deposition to obtain a metal and non-metal cascade catalyst having a Fe-B dual site.
2. The preparation method according to claim 1, characterized in that: The percentage of iron in the iron source to the mass of graphene oxide in the graphene oxide solution is 1-10%; the percentage of boron in the boron source to the mass of graphene oxide in the graphene oxide solution is 1-7%.
3. The preparation method according to claim 1 or 2, characterized in that: The iron source is ferric nitrate; the boron source is boric acid.
4. The preparation method according to claim 1, characterized in that: In step S1, the ultrasonic time is 10 minutes.
5. The preparation method according to claim 1, characterized in that: In step S1, the temperature of the hydrothermal reaction is 170-190° C., and the time of the hydrothermal reaction is 8-14 hours;.
6. The preparation method according to claim 1, characterized in that: In step S2, the freeze-drying treatment time is 5-10 hours.
7. The preparation method according to claim 1, characterized in that: In step S2, the high-temperature nitridation using chemical vapor deposition method includes the following steps: nitridation is carried out in a mixed atmosphere of argon and ammonia, the reaction temperature is 700-900°C, the reaction time is 1-3h, the argon flow rate is 100±10sccm, and the ammonia flow rate is 50±10sccm.
8. A metal and non-metal cascade catalyst having a Fe-B dual site, prepared by the preparation method according to any one of claims 1 to 8.
9. Use of the metal and non-metal cascade catalyst having Fe-B dual sites as claimed in claim 8 as a catalyst for four-electron oxygen reduction reaction.
10. Use of the metal and non-metal cascade catalyst with Fe-B dual sites as claimed in claim 8 as a cathode catalyst for zinc-air batteries.
Citation Information
Patent Citations
Preparation method of boron nitrogen doped graphene supported palladium catalyst
CN105833893A
Graphene loaded ruthenium catalyst, preparation method and application
CN109482214A
Electro-Fenton catalyst and preparation method and application thereof
CN112295573A
Single atom catalyst having double active sites and method of fabricating the same
US20240287691A1